Формування національної доктрини цивільного процесу в роботах науковців Київського національного університету імені Тараса Шевченка в період незалежності України - Притика, Ю. Д.; Ізарова, Ірина Олександрівна (Київський національний університет імені Тараса Шевченка, 2021)
Мета проведеного дослідження – установити внесок науковців-правників Київського національного університету імені Тараса Шевченка у розвиток доктрини науки цивільного процесуального права в період незалежності України, з 1991 року. Для реалізації цієї мети застосовано наукові методи аналізу основних законодавчих актів, що регулюють цивільні процесуальні відносини, виокремлено й охарактеризовано положення тих досліджень, в яких було запропоновано нові підходи до вдосконалення механізму реалізації права особи на справедливий суд, забезпечення доступу до правосуддя в цивільних справах, розвиток і вдосконалення цивільного судочинства в умовах забезпечення сучасних міжнародних, зокрема європейських, підходів. Результатами проведеного дослідження виявлено більше 40 дисертаційних досліджень, що були захищені впродовж обраного періоду в Київському університеті, а також багато наукових досліджень, що істотно вплинули на розвиток національної традиції цивільного процесу. Підбито підсумки проведеного дослідження та визначено напрями подальшого розвитку наукових пошуків у сфері цивільного процесуального права України.

The event of the thirtieth anniversary of Ukraine's independence [1] provides an excellent opportunity to sum up the interim results, analyse the achievements made in building an independent democracy, as well as to understand the miscalculations that can hardly be avoided. Legal science plays a huge role in this, particularly, its part related to the field of administration of justice in civil cases which is ensuring the effective settlement of civil disputes and the administration of civil justice. In view of this, the purpose of the study is to establish the contribution of legal scholars of Taras Shevchenko National University of Kyiv in the development of the doctrine of the science of civil procedural law during the period of independence of Ukraine since 1991. To achieve this goal, scientific methods of analysis of the main legislative acts regulating civil procedural relations were used, the provisions of those studies were singled out and characterized; the latter proposed new approaches to improving the mechanism of exercising the right to a fair trial, ensuring access to justice in civil cases; development and improvement of civil justice in the context of modern international, in particular, European approaches. The results of the study revealed more than forty dissertation researches, which were promoted during the selected period at the University, as well as a number of scientific studies that significantly influenced the development of the national tradition of civil procedure. The conclusions summarize the results of the study and identify areas for further development of research in the field of civil procedural law of Ukraine. In particular, it is noted that today special attention should be paid to the need for proper implementation in Ukraine of the concept of the right of everyone to a fair trial, guaranteed by the European Convention, as well as to increase out-of-court settlement of disputes mediating the right to access and freedoms in the modern world. It is important to understand the global trend of reconciliation of the parties as the most effective settlement of disputes and the spread of various ways that allow the parties to find the most convenient and effective way to protect their rights.
Formation of the national doctrine of civil procedure in the works of scientists of Kyiv University during the independence of Ukraine
Affiliation: Київський національний університет імені Тараса Шевченка, Київ, Україна
Keywords: цивільний процес; Україна; доступ до правосуддя; правова доктрина; Київський університет; Цивільний процесуальний кодекс України; civil process; Ukraine; access to justice; legal doctrine; Kyiv University; Civil Procedure Code of Ukraine